PENGEMBANGAN APLIKASI WEB JENAK! (OJEK ANAK): SOLUSI TRANSPORTASI AMAN DAN EFISIEN UNTUK ANAK-ANAK - Salsabilla Varadinta; Mohammad Ibrahim Sugiyanto (LPPM Universitas Abdurrab, 2025)
Transportation as an important aspect in everyday life, especially with the increasing population growth. Although public transportation exists, there are still many obstacles such as long waiting times and inconsistent punctuality as well as minimal safety of public transportation for children. In this context, the development of a web-based application Jenak! (Online Ojek Anak) offers an innovative solution to facilitate the delivery of children to school with delivery activities that can be tracked by parents in real time with user security features using driver verification to application users. The development method used is waterfall, including the stages of analysis, design, coding, and testing. This application is designed to improve the efficiency and effectiveness of delivery, with a focus on ease of access and safety of children during the trip. It is hoped that Jenak! can provide a practical solution for parents and schools in managing child delivery activities safely and efficiently in the future, the potential of this application can replace conventional child pick-up and drop-off services or public transportation which are still far from safe and efficient transportation for children.